2016
DOI: 10.1523/jneurosci.0936-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

PtenRegulates Retinal Amacrine Cell Number by Modulating Akt, Tgfβ, and Erk Signaling

Abstract: All tissues are genetically programmed to acquire an optimal size that is defined by total cell number and individual cellular dimensions. The retina contains stereotyped proportions of one glial and six neuronal cell types that are generated in overlapping waves. How multipotent retinal progenitors know when to switch from making one cell type to the next so that appropriate numbers of each cell type are generated is poorly understood. Pten is a phosphatase that controls progenitor cell proliferation and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 81 publications
(52 reference statements)
4
43
0
Order By: Relevance
“…activated the survival signaling pathway. PTEN is a negative regulator of AKT phosphorylation (27). The accumulation of PTEN attenuates AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…activated the survival signaling pathway. PTEN is a negative regulator of AKT phosphorylation (27). The accumulation of PTEN attenuates AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that rapamycin upregulates Akt phosphorylation ( Leipert et al, 2016 ; O'Reilly et al, 2006 ; Schmid et al, 2014 ), which is already elevated in Pten cKO retinas ( Cantrup et al, 2012 ; Tachibana et al, 2016 ). We thus asked whether pAkt levels were further increased in animals treated with rapamycin.…”
Section: Resultsmentioning
confidence: 96%
“…We previously reported the generation of a Pten cKO using a Pax6::Cre driver that is more active in the peripheral versus central retina ( Cantrup et al, 2012 ; Marquardt et al, 2001 ; Tachibana et al, 2016 ). Strikingly, we noted that, in postnatal day (P)21 Pten cKO mice ( Pten fl/fl ;Pax6::Cre + ), a bulge-like ectopic mass developed in a site-specific manner on the dorsal-medial retinal surface in a completely penetrant manner ( n =49/49; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also used the heterochronic pellet assay to examine how amacrine cell feedback signals are themselves regulated. We found that Pten is an essential positive regulator of amacrine cell differentiation, and using the pellet assay, we demonstrated that Pten acts in RPCs to control responsiveness to Tgfβ2 signaling (Tachibana et al, 2016). Understanding how amacrine cells and RPCs interact provides important new insights into how cell number is controlled in the retina.…”
Section: Introductionmentioning
confidence: 90%
“…We have used this assay to demonstrate that sonic hedgehog (Shh), which we found acts as a negative regulator of retinal ganglion cell (RGC) differentiation, promotes RPC proliferation (Jensen and Wallace, 1997;Ringuette et al, 2014). More recently we modified the heterochronic pellet assay to assess the role of feedback signals for retinal amacrine cells, identifying transforming growth factor β2 (Tgfβ2) as a negative feedback signal, and Pten as a modulator of the Tgfβ2 response (Ma et al, 2007;Tachibana et al, 2016). This assay can be adapted to other lineages and tissues to assess cell-cell interactions between two different celltypes (heterotypic) in either an isochronic or heterochronic manner.…”
Section: Introductionmentioning
confidence: 99%